(untitled) (The Review of Diabetic Studies, 2024)
Background: Diabetic foot is a foot that shows any pathology that consequence in a straight line from diabetes mellitus or any long -term complications of DM which lead to diabetic foot amputation when delaying in treatment. Aim of the study: Was to assess self-care practices of Saudi diabetic foot patients. Research design: A descriptive research design was utilized to conduct this study. Setting: This study was conducted at Diabetic Patient Clinic of Taif hospital, Saudi Arabia. The sample: A systematic sample of 200 diabetic foot patients over 50 years old. Tools: One tool was used in this study. 1): A structured interviewing questionnaire which consists of four parts. Part (1): Demographic characteristics of diabetic foot patients, Part (2): Medical history of diabetic foot patients. Part (3): Patients’ knowledge about diabetes Mellitus and diabetic foot. Part (4): Diabetic patients’ reported practices toward diabetic foot self- care. Results: 46.5% of studied patients aged from60<70 years old, 47.5% of them had basic education, and 50% of them were male.52% of studied patients had diabetes mellitus from 1to less than 5 years and 35% of them were visiting The Diabetic Clinic every three weeks Also 49.5% of studied patients had poor total knowledge level, while; 51% of them had satisfactory total reported self-care practices regarding diabetic foot care. Conclusion: There was highly statistically positive correlation between total knowledge of studied patients, their total reported practices regarding care of diabetic foot. Recommendations: Develop health educational program for diabetic foot patients to increase their knowledge and self -care practices regarding diabetic foot.